Preventing infections in non-hospital settings: long-term care. - Nicolle, L E (Centers for Disease Control and Prevention, 2001)
Infection concerns in long-term care facilities include endemic infections, outbreaks, and colonization and infection with antimicrobial-drug resistant microorganisms. Infection control programs are now used in most long-term care facilities, but their impact on infections has not been rigorously evaluated. Preventive strategies need to address the changing complexity of care in these facilities, e.g., the increased use of invasive devices. The anticipated increase in the elderly population in the next several decades makes prevention of infection in long-term care facilities a priority.